2011
DOI: 10.1007/s11661-011-0940-4
|View full text |Cite
|
Sign up to set email alerts
|

Using a Two-Phase Columnar Solidification Model to Study the Principle of Mechanical Soft Reduction in Slab Casting

Abstract: A two-phase columnar solidification model is used to study the principle of mechanical soft reduction (MSR) for the reduction of centerline segregation in slab casting. The two phases treated in the model are the bulk/interdendritic melt and the columnar dendrite trunk. The morphology of the columnar dendrite trunk is simplified as stepwise growing cylinders, with growth kinetics governed by the solute diffusion in the interdendritic melt around the growing cylindrical columnar trunk. The solidifying strand sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 19 publications
(42 reference statements)
0
56
0
Order By: Relevance
“…3 is another important factor which influences the SR effect, because most of SR amount is consumed on the bloom deformation process. 15,18,19) The SR efficiency η i is defined to characterize the relationship between SR amount on the strand surface and the required SR amount of the shrinkage volume. 18,20) According to the authors' previous work, 19,21) Where, R i is the surface SR amount in i th SR point shown in Fig.…”
Section: Sr Amount Calculation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…3 is another important factor which influences the SR effect, because most of SR amount is consumed on the bloom deformation process. 15,18,19) The SR efficiency η i is defined to characterize the relationship between SR amount on the strand surface and the required SR amount of the shrinkage volume. 18,20) According to the authors' previous work, 19,21) Where, R i is the surface SR amount in i th SR point shown in Fig.…”
Section: Sr Amount Calculation Modelmentioning
confidence: 99%
“…[12][13][14][15][16] Recently, Menghuai Wu and et al 15,16) developed a two-phase columnar solidification model to describe the effect of shell deformation, melt flow, dendrite growth on the macro-segregation behavior, and revealed more detailed mechanism and principles of SR. However, due to the complicated coupled macro and micro factors and variable industrial process, it is still difficult to precisely quantify the SR amount, and more studies were carried out with industrial trial method.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, external deformation can be beneficial such as the application of a 'soft reduction', a small rolling reduction (e.g. a few % strain) near to the end of the sump to compensate for solidification shrinkage and reduce centreline segregation and porosity [6][7][8]. Despite this importance, there remains only limited understanding of the mechanical behaviour of the mushy-zone in steels and, in particular, of their microstructural response to load and how this leads to defects.…”
Section: Introductionmentioning
confidence: 99%
“…Favourable results have been obtained by applying the described models to quantitatively predict macrosegregation in cast alloys. [12][13][14][15][16] Solute redistribution occurring at a moving solid-liquid interface, calculated by the microsegregation model, is known to play a significant role in the modeling of mac-rosegregation. A few microsegregation models, including the Lever rule, Gulliver-Scheil equation (Scheil), Brody-Flemings (BF) model, Ohnaka model, Clyne-Kurz (CK) model and Voller-Beckermann (VB) model, are reported in previous works.…”
Section: Introductionmentioning
confidence: 99%